Effect of heat treatment temperature and turning residual stresses on the plain and notch fatigue strength of Ti-6Al-4V additively manufactured via laser powder bed fusion. (September 2022) - Emanuelli, L.; Molinari, A.; Facchini, L.; Sbettega, E.; Carmignato, S.; Bandini, M.; Benedetti, M.
Highlights: Effect of 3 heat treatment temperatures on tensile and fatigue properties. They mostly affect ductility, tensile strength and electric power consumption. Notch and plain fatigue strength controlled by turning residual stresses and defects. Effect of defects well captured by Murakami sqrt(area) model. Notch fatigue well predicted by the theory of critical distances. Abstract: This paper investigates the fatigue strength of plain and notched specimens produced via laser powder bed fusion and heat-treated at different temperatures ranging between 800 °C and 950 °C. The effects of internal defectiveness and turning residual stresses are explored through computed tomography and X-ray diffraction. Residual stresses are eliminated in part of the experimental batches through a stress relief. The surface compressive residual stresses push the fatigue crack initiation site below the outer surface and increase the fatigue strength of the notched specimens. The heat-treatment temperature affects mostly the total elongation and the energy consumption, whereas its influence on the fatigue strength is less evident.